Preserving Legacy: The Impact of Royal Waqf on Cultural Heritage Conservation in Sumedang Larang - Yusep Rafiqi; Ari Farizal Rasyid; Agus Ahmad Nasrulloh; Iis Marwan (UIN Sunan Gunung Djati, 2025)
This article investigates the underexplored role of waqf in preserving cultural artifacts within the context of Indonesian waqf regulations, with a specific emphasis on royal waqfs. It examines the distinct contributions of royal waqfs to the preservation of cultural heritage. It offers a contextual analysis within the legal and historical boundaries of Indonesian waqf traditions. This article utilizes ethnography methods, which involve conducting extensive fieldwork consisting of in-depth interviews and direct observations at the Sumedang Larang Palace and the Prince of Sumedang Waqf's Nazir Foundation. These methodologies helped to achieve a detailed comprehension of the operating dynamics and conservation procedures of royal waqfs. This article emphasizes two crucial activities that are necessary for the protection of waqf assets: conservation and asset restoration. This indicates that these efforts are crucial for preserving the structural stability and cultural significance of historical artifacts that are handled under royal waqfs. The article also highlights the challenges and approaches required to combine traditional waqf principles with modern preservation requirements. This article enhances the overall discussion on cultural heritage management by suggesting a specific governance model designed for waqf institutions associated with royal families. This resource provides practical knowledge and frameworks that may be customized by waqf managers in different regions of Indonesia. Its goal is to improve the effectiveness of waqf in the protection of cultural heritage. This work is an important resource for policymakers, cultural heritage specialists, and waqf administrators who want to link waqf management with cultural conservation goals.